Prospective evaluation for respiratory pathogens in children with sickle cell disease and acute respiratory illness. Issue 3 (4th October 2013) - Srinivasan, Ashok; Wang, Winfred C.; Gaur, Aditya; Smith, Teresa; Gu, Zhengming; Kang, Guolian; Leung, Wing; Hayden, Randall T.
Abstract Background Human rhinovirus (HRV), human coronavirus (hCoV), human bocavirus (hBoV), and human metapneumovirus (hMPV) infections in children with sickle cell disease have not been well studied. Procedure Nasopharyngeal wash specimens were prospectively collected from 60 children with sickle cell disease and acute respiratory illness, over a 1‐year period. Samples were tested with multiplexed‐PCR, using an automated system for nine respiratory viruses, Chlamydophila pneumoniae, Mycoplasma pneumoniae, and Bordetella pertussis. Clinical characteristics and distribution of respiratory viruses in patients with and without acute chest syndrome (ACS) were evaluated. Results A respiratory virus was detected in 47 (78%) patients. Nine (15%) patients had ACS; a respiratory virus was detected in all of them. The demographic characteristics of patients with and without ACS were similar. HRV was the most common virus, detected in 29 of 47 (62%) patients. Logistic regression showed no association between ACS and detection of HRV, hCoV, hBoV, hMPV, and other respiratory pathogens. Co‐infection with at least one additional respiratory virus was seen in 14 (30%) infected patients, and was not significantly higher in patients with ACS (P = 0.10). Co‐infections with more than two respiratory viruses were seen in seven patients, all in patients without ACS. Bacterial pathogens were not detected. Conclusion HRV was the most common virus detected in children with sickle cell disease and acute respiratory illness, and was not associated with increased morbidity. Larger prospective studies with asymptomatic controls are needed to study the association of these emerging respiratory viruses with ACS in children with sickle cell disease. Pediatr Blood Cancer 2014;61:507–511. © 2013 Wiley Periodicals, Inc.